Early human impact in the Azores Archipelago: A Late Holocene high-resolution paleoecological analysis from Lake Peixinho, Pico Island, Portugal - de Boer, E.J.; Rull, Valentí; Van Leeuwen, F. N.; Amaral-Zettler, Linda; Bao, Roberto; Birlo, S.; Gonçalves, Vítor; Hernández, Armand; Martin-Puertas, Celia; Pla-Rabes, Sergi; Pueyo Mur, Juan José; Raposeiro, P. M.; et al. (2018)
Human arrival on oceanic islands causes large-scale habitat alterations and extinctions of local flora and fauna. Understanding the processes of how humans transformed island environments soon after colonization is critical to current conservation and restoration strategies. Only a few islands worldwide provide the opportunity to examine island colonization within a period of recorded history. Such islands enable us to calibrate paleoecological methods and perform comparative analyses with other locales. According to the written sources, the Portuguese officially colonized the Azores Archipelago in the North Atlantic Ocean in the 15th century providing a well-documented history of human impact. Paleoecological reconstructions from the Azores thus allow us to compare ecosystem processes and dynamics before and after colonization. A high-resolution pollen record from Lake Peixinho (Pico Island) provides novel insights into early human impacts in the Azores from the 13th century – two centuries prior to the official historical colonization of the archipelago. In addition, the record highlights the role of tephra sedimentation from proximal volcanic eruptions as natural driver of ecosystem dynamics. We compared palynological results to diatom, chironomid, Cladocera and geochemical records from the same lake, as well as other sedimentary records from Pico Island and existing pollen records from other Azorean islands. Ongoing analyses of paleoecological records from other islands in the Azorean Archipelago (Corvo, Flores, Sao Miguel, and Terceira) will help pinpoint the timing and impact of human colonization in the Azores. This research is funded by the Juan de la Ciervaformacion postdoctoral grant (FJCI-2015-26199), the Fundacao LUSO-Americana, and through the Spanish funded research projects PaleoNAO (CGL2010-15767), RapidNAO (CGL2013- 40608-R) and PaleoModes (CGL2016-75281-C2). Peer Reviewed